Engaging university students in hands on learning practices and social media collaboration - Dominic, D.D. (Institute of Electrical and Electronics Engineers Inc., 2016)
this manuscript emphasizes on incorporating the hands on learning practices using information communication technology (ICT) tools and collaborative learning using social media technologies, in university educational courses such as Statistics & Empirical Methods. From the students' perspective, digital knowledge acquiring experience motivates learning capabilities and develops required scholastic skills. Introduction to software for analytical problem solving, and establishing communication channel using available online collaborative technologies can aid in enriching university teaching and learning experience. The results of use of ICT in university courses have shown substantial difference among the two participating groups; each comprised of twenty five students from the Statistics & Empirical Methods course. The experimental group performed significantly better than the controlled group, after going through series of tests and evaluations. The findings suggest that hands on learning experience blended with collaborative learning are essentially constructive for university courses and prepare university students for applied workplaces. Â© 2016 IEEE.